APPLICATION OF PHYSICAL LABORATORY PROCESSES OF ROBOTICS IN PROFESSIONAL EDUCATIONAL ORGANIZATIONS - Norqo'ziyev, Q (Журнал математики и информатики, 2023)
This article examines the use of robotics elements in the educational process of physical science in professional educational institutions, as well as the features of using robotics laboratory equipment in physical science laboratory work in professional educational institutions. By introducing elements of robotics into education, special attention was paid to increasing the creative activity of students, and laboratory equipment suitable for today's requirements is used.